Collaborative Governance of Coral Reef Management and Rehabilitation in Tsunami Disaster Mitigation Efforts - Dodi Robby Hari Ismanto; Rachma Fitriati (Program Pascasarjana Universitas Negeri Makassar, 2020)
The tsunami is the biggest threat to countries around the world tectonic plates and the ring of fire, including Indonesia. The impact of economic losses and heavy casualties made the tsunami worth watching out. Ecosystem-based tsunami disaster mitigation efforts are deemed necessary, considering that 2/3 of Indonesia consists of the sea. The coral reef is one of the coastal ecosystems that can reduce tsunami waves by up to 50% before it hits coastal areas. However, the current condition of coral reefs is very alarming due to the actions of irresponsible humans. Collaboration between stakeholders is needed to carry out ecosystem-based tsunami disaster mitigation efforts. Collaborative governance becomes an essential issue in efforts to build and improve services in the public sector by involving all relevant stakeholders. The sectoral ego of the stakeholders is no longer relevant to be maintained because each actor has their strengths and weaknesses. Collaboration between actors framed in a collaboration platform by having a principled engagement, shared motivation, and collective capacity will produce better results.